P849 Urease-positive proteobacteria in Crohn's disease identified by novel ex vivo mucosal microbe culture combined with metagenomic sequencing (MC-MGS): the ENIGMA study. (25th January 2019) - Berendsen, E M; Hoedt, E C; Teh, J-J; Zhang, J; Zhang, F; Liu, Q; Hamilton, A L; Ching, J; Sung, J J; Yu, J; Ng, S C; Kamm, M A; et al.
Abstract: Background: Longitudinal 16S analysis of Australian Crohn's disease patients suggest that the presence of Proteus spp. is predictive of, and associated with, Crohn's disease recurrence after intestinal resection. 1 This bacterium is remarkable for its urease production, recently identified as a key functional change. 2 Further characterisation of the mucosa associated microbiome (MAM) using metagenome sequencing has been limited by the overwhelming presence of human DNA. Here, we present a novel approach, microbe-culture metagenome sequencing (MC-MGS), to characterise and confirm bacteria associated with urease activity in the mucosa-associated microbiota in Crohn's disease. Methods: Anastomotic biopsies from 5 Crohn's disease patients 6 months post-surgery, were stored in RNA later for DNA extraction. Matched biopsies stored in an anaerobically prepared glycerol buffer underwent microbe culture with a habitat-simulating medium (37ºC, 24 h). Total and microbe enriched biopsy DNA, as well as MC-DNA, was sequenced to a depth of 3 gbp as 150 bp paired-end reads with the Illumina NextSeq500 platform. In addition to metagenome-assembled genomes produced using MetaBAT, 3 urease-producing (and other) bacteria were isolated using selective media under aerobic and anaerobic conditions. Results: MC-MGS produced 16 metagenome assembled genomes representing a broad diversity of bacteria representing both facultative and fastidious anaerobes, including members of the Proteeae tribe ( Providencia/Morganella ). Axenic isolates of urease-positive bacteria were also recovered from the cultures produced from 3/5 biopsies, and included strains of Klebsiella pneumoniae, Escherichia fergusonii, Morganella morganii and Enterococcus faecium . Conclusions: Urease-positive bacteria, principally members of the Enterobacteriaceae are associated with Crohn's disease. New combined culture and metagenomic sequencing techniques provide a holistic and functional characterisation of the IBD mucosa-associated microbiota, while also providing metagenome-assembled genomes, microbial consortia, and axenic isolates relevant to understanding Crohn's disease pathophysiology. This work is supported by The Leona M. and Harry B. Helmsley Charitable Trust References 1. Wright EK, et al., Microbial factors associated with postoperative Crohn's disease recurrence. J Crohn's Colitis 2017;11:191–203. 2. Ni J, et al. A role for bacterial urease in gut dysbiosis and Crohn's disease. Sci Transl Med 2017:9. 3. Kang DD, Froula J, Egan R, et al . MetaBAT, an efficient tool for accurately reconstructing single genomes from complex microbial communities. PeerJ 2015;3:e1165.